Prinsip Reward dan Punishment dalam Surat Al-Bayyinah - Rahmah, Mawaddatur; Fithriyah, Nur Nafisatul; Mufidah, Nadzirotul (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2021)
God's justice is not that He follows the laws of justice predetermined, but that it means that God is the source of justice. Justice is not a measure of God's deeds, but His deeds are a measure of that justice. As for the Mu'tazilah, they have a different opinion. They argue that justice is an independent essence. According to them, Allah will carry out all His deeds by following the standard of justice because He has the nature of Wisdom and Justice. Al-Qur'an reveals the manifestation of Allah's justice through its verses.